The Role of Students' Green Mindset in Protecting Nature - Utami, Rezki Aguswidya; Wahyuni, Tri; Lianawati, Lianawati; Hidayati, Zakiah; Hasanah, Nurul (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
Generation Z, which is synonymous with the internet and cyberspace, also has concern for the environment. This study aims to describe the role of students’ green mindset in protecting nature in their fourth semester. This study uses a qualitative, naturalistic paradigm. Primary data was taken from participatory observations of 107 students in the 2020 and 2021 classes of the Islamic Communication and Broadcasting study program and interviews with 11 of them. The results of this study were: (1) They have a growth mindset to protect nature; (2) The green mindset they have had has been implemented with real behavior, namely holding deliberations with faculty student organizations to protect the surrounding environment, educating elementary school-age children to sort out the trash around them, doing a simple campaign on the social media they have, writing green in online media, and carrying out real actions in the field (planting plant seeds around the faculty and inviting campus residents to collect cooking oil waste). Overall, students' green mindsets should be cultivated by providing a green curriculum with several green courses to manage environmental challenges.